Indications and Use of Isotretinoin in Facial Plastic Surgery - Heppt, Markus V.; Kirchberger, Michael C.; Ruzicka, Thomas; Berking, Carola; Heppt, Werner J. (Facial Plastic Surgery, 2018)
Isotretinoin is a first generation retinoid with pleiotropic effects on keratinocyte differentiation, proliferation, and activity of sebaceous glands. For years, there has been intense debate on whether the use of isotretinoin combined with cosmetic or surgical procedures is safe and potentially more efficient than either therapy alone. Due to delays in wound healing and keloid formation, conservative recommendations were not to combine isotretinoin with any plastic surgery or local treatment at 6 to 12 months after discontinuation of the drug. However, there is increasing evidence that a combination approach is not only safe, but may also provide excellent cosmetic outcomes in acne scars, sebaceous gland hyperplasia, and thick-skinned patients undergoing facial plastic surgery. In particular, low-dose regimens of isotretinoin may offer advantages over standard dosage treatments because of better tolerability and safety in long-term use adjunct with surgical interventions. In this article, the authors aim to summarize the current evidence on the use of isotretinoin in facial plastic surgery and to share their experience from selected patients.
Keywords: isotretinoin; acne; scars; laser; facial plastic surgery